2010
DOI: 10.5172/jmo.2010.16.4.601
|View full text |Cite
|
Sign up to set email alerts
|

A model for improving board performance: The case of a national sport organisation

Abstract: The transition of many sport organisations from being predominantly volunteer-administered and anchored in an amateur ethos to professionally managed entities has created unique challenges for the governance of sport. This paper provides a contribution to the governance literature through the presentation of a situational case where a four-stage model, drawn from an action research approach, has been used for developing a board's strategic capability and subsequent improvement in organisational performance. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 80 publications
0
3
0
3
Order By: Relevance
“…Frazer ( 2000 ) suggested that a strength of communitarianism is the possibility of a coalition of diverse groups (of thought and action) around the idea of a greater good. Within the context of sport, this is an important consideration given that provision and delivery of participation opportunities or engagement more broadly (e.g., as fans) often involves contributions from and collaborations between many stakeholders from the public, private, and voluntary sectors (Ferkins et al, 2010 ).…”
Section: Theorizing Communitymentioning
confidence: 99%
“…Frazer ( 2000 ) suggested that a strength of communitarianism is the possibility of a coalition of diverse groups (of thought and action) around the idea of a greater good. Within the context of sport, this is an important consideration given that provision and delivery of participation opportunities or engagement more broadly (e.g., as fans) often involves contributions from and collaborations between many stakeholders from the public, private, and voluntary sectors (Ferkins et al, 2010 ).…”
Section: Theorizing Communitymentioning
confidence: 99%
“…Assim, influenciam a forma como as organizações são dirigidas, incluindo também as organizações esportivas (CHADWICK, 2009;SHILBURY, 2012;MCDONALD, 2009;HEALEY, 2012;MICHIE;OUGHTON, 2005;TAYLOR;O'SULLIVAN, 2009;WALTERS;SHILBURY, 2010 Sob a ótica da gestão e controle, os autores Shilbury e Ferkins (2011) demonstraram a transição do esporte amador para um esporte profissional, em organizações esportivas da Nova Zelândia. Observaram que a gestão e o controle são essenciais para nortear as organizações esportivas, impactando na melhor compreensão das estratégias trabalhadas pelos Conselhos de Administração, e que, por sua vez, refletem-se nas tomadas de decisões futuras, tornando essas entidades mais profissionais.…”
Section: Gestão E Controle Nas Organizações Esportivasunclassified
“…Diante do exposto, realça-se que o mecanismo de governança mais importante para o desenvolvimento e/ou aperfeiçoamento da governança nas instituições esportivas é o Conselho de Administração, mais propriamente devido à sua relação e importância para o fomento da política, formulação, implementação e adoção da estratégia nestas organizações (Ferkins et al, 2005(Ferkins et al, , 2009(Ferkins et al, , 2010Taylor e O'Sullivan, 2009;Ferkins e Shilbury, 2012), gerando valor para elas (Stadtmann, 2006).…”
Section: Governança Corporativa Nos Esportes: Análise Dos úLtimos 23 unclassified
“…Portanto, é tangível que a Governança Corporativa se aplique no esporte (Leopkey e Parent, 2012), mitigando possíveis conflitos de interesse (Rezende et al, 2009), atribuindo maior capacidade de melhora da performance da gestão do Conselho de Administração (Taylor e O'Sullivan, 2009;Ferkins e Shilbury, 2012), nas organizações desportivas (Ferkins et al, 2010), influenciando na execução da estratégia (Ferkins e Shilbury, 2012;Ferkins et al, 2009), nas tomadas de decisão (Kikulis, 2000), na eficácia organizacional (Ferkins et al, 2005), criando, a posteriori, valor aos stakeholders (Stadtmann, 2006).…”
Section: Introductionunclassified